Carbohydrate Loading to Combat Acute Pancreatitis. Issue 10 (October 2018) - Vervliet, Tim; Yule, David I.; Bultynck, Geert
Abstract : Acute pancreatitis is characterized by ATP deficiency and sustained Ca 2+ overload in pancreatic acinar cells, leading to premature zymogen activation, auto-digestion of the pancreas, and necrosis. Recent research reveals a rational approach to ameliorate disease through galactose feeding, bypassing hexokinases to restore ATP levels and Ca 2+ homeostasis, thereby reducing disease markers.